IDENTIFIKASI VARIASI FENOTIPIK AYAM KAMPUNG CARU DI BALI - Sarini N. P.; I W. Wijana; N. M. A. Rasna; I N. Ardika (Fakultas Peternakan Universitas Udayana, 2019)
This study aimed to identify phenotypic variation of kampung chicken caru. This study was held at farmers,collectors and vendors kampung chikens in animal market in Bali. Phenotypic factors identified were comb types,feather, beak, and shank colors. The quantitative characters that were body mass and dimential. The qualitativedata collected was grouped the variation and the quantitative data then analyzed using descriptive quantitative andthe coefficient of variation was calculated. Black caru chicken had single and rose combs with beak and shank colorwere black and yellow. Whereas, red caru chicken had single, pea and rose combs with beak and shank color wereblack, white and yellow. For yellow caru chicken the comb was single and pea with the beak and shank were yellow.White caru chicken had single and pea combs with the color of the beak and shank were white. Similar to blackcaru, brumbun also chicken had single and pea comb with the color of beak and shank were black, white and yellow.Tibia length of brumbun caru chicken was vary (CV>15%) whereas wing length of red caru chicken was uniform(CV<15%). In conclusion, kampung caru chiken had vary of penothipic variation.